2020
DOI: 10.1016/j.isci.2020.101581
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Activity of Cyclophilin A Impedes Prolactin Receptor-Mediated Signaling, Mammary Tumorigenesis, and Metastases

Abstract: Summary Prolactin (PRL) and its receptor (PRLr) play important roles in the pathogenesis of breast cancer. Cyclophilin A (CypA) is a cis-trans peptidyl-prolyl isomerase (PPI) that is constitutively associated with the PRLr and facilitates the activation of the tyrosine kinase Jak2. Treatment with the non-immunosuppressive prolyl isomerase inhibitor NIM811 or CypA short hairpin RNA inhibited PRL-stimulated signaling, breast cancer cell growth, and migration. Transcriptomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…WT-STAT5a PRL-induced or inhibited genes were compared to previous PRL-transcriptomic data released by our laboratory, such that after matching the criteria that the DEG be present in at least two datasets, 105 putative PRL-regulated genes were identified (Supplemental Table S4 ) 38 , 39 . A subset of these genes were used to identify functionally-enriched pathways with PRL treatment that may be changed by expression of the STAT5a mutants through Ingenuity Pathway Analysis (IPA, Qiagen, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WT-STAT5a PRL-induced or inhibited genes were compared to previous PRL-transcriptomic data released by our laboratory, such that after matching the criteria that the DEG be present in at least two datasets, 105 putative PRL-regulated genes were identified (Supplemental Table S4 ) 38 , 39 . A subset of these genes were used to identify functionally-enriched pathways with PRL treatment that may be changed by expression of the STAT5a mutants through Ingenuity Pathway Analysis (IPA, Qiagen, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a phase I clinical trial, the monoclonal antibody LFA102, a humanized neutralizing monoclonal antibody directed against the extracellular domain of PRLR, was tested in patients with advanced BC (10), which had previously caused tumor shrinkage in an in vivo model of BC (11). In vitro and in vivo, preclinical reports suggest that the PRL-PRLR union is vital for breast carcinogenesis (9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in the clinical area, LFA102 had no anti-tumor effect when administered as a single agent in patients with PRLRpositive metastatic BC, questioning the role of PRL in the development of BC and highlighting the need for further studies to fully understand the role of PRLR-driven signaling cascades in tumor growth (10).…”
Section: Prl As a Therapeutic Target Pro-or Anti-tumor?mentioning
confidence: 99%
“…PRL promotes the initiation and progress of different gynecological neoplasms through different mechanisms. Furthermore, it is known that they share the cellular effects exerted through the JAK/STAT signaling cascade, such as survival, cell cycle progression, proliferation, migration, high metabolic rates, angiogenesis, and anti-apoptosis (9,12,(29)(30)(31)(32)(33)(34)(35)(36). In addition to this, it has been found that the PRLR is overexpressed in breast (14,37), cervical (38)(39)(40), ovarian (41,42), and endometrial cancer (EC) (2,43) in comparison with their respective cancer-free tissues.…”
Section: Effect Of Prl On Mechanisms That Promote Gynecological Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this enzyme has been shown to be a key molecule in multiple biological functions, including molecular chaperoning,protein folding,protein tra cking,immune modulation,and cell signaling [6]. Studies have also reported that PPIA is involved in several diseases, including kawasaki disease [7],amyotrophic lateral sclerosis [8],atherosclerosis,myocardial infarction [9],severe sepsis [10],vascular smooth muscle cell disease [11],rheumatoid arthritis and HIV infection [12].Moreover,several studies have shown that PPIA is expressed in some cancers,including lung cancer,nasopharyngeal carcinoma [13],gastric adenocarcinoma [14],thyroid carcinoma [15],neuroblastoma [16],ovarian cancer [17],pancreatic cancer [18],breast cancer,colorectal cancer [19][20],melanoma [21],liver hepatocellular carcinoma [22].Many researchers have assessed PPIA function in cancer.It has been suggested that PPIA plays an important role in the whole pathological process of cancer development.High expression levels of PPIA were associated with decreased overall survival in liver hepatocellular carcinoma,colorectal cancer,low-grade glioma, acute myeloid leukemia.However,in gastric adenocarcinoma, high expression levels of CypA are positively correlated with invasiveness and distant metastasis.Therefore,both low and high expression of PPIA are associated with tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%